2022
DOI: 10.1155/2022/4444513
|View full text |Cite
|
Sign up to set email alerts
|

Perilla Fruit Water Extract Attenuates Inflammatory Responses and Alleviates Neutrophil Recruitment via MAPK/JNK-AP-1/c-Fos Signaling Pathway in ARDS Animal Model

Abstract: Airway respiratory distress syndrome (ARDS) is usually caused by a severe pulmonary infection. However, there is currently no effective treatment for ARDS. Traditional Chinese medicine (TCM) has been shown to effectively treat inflammatory lung diseases, but a clear mechanism of action of TCM is not available. Perilla fruit water extract (PFWE) has been used to treat cough, excessive mucus production, and some pulmonary diseases. Thus, we propose that PFWE may be able to reduce lung inflammation and neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It has been established that the effective ingredients of AHCHOS are ambroxol hydrochloride and clenbuterol hydrochloride, which are representative drugs for symptomatic treatment. AHCHOS, as a mucus motility enhancer, can promote airway cilia oscillation, improve mucus clearance kinetics, and help expel phlegm 55 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been established that the effective ingredients of AHCHOS are ambroxol hydrochloride and clenbuterol hydrochloride, which are representative drugs for symptomatic treatment. AHCHOS, as a mucus motility enhancer, can promote airway cilia oscillation, improve mucus clearance kinetics, and help expel phlegm 55 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the effective ingredients of AHCHOS are ambroxol hydrochloride and clenbuterol hydrochloride, which are representative drugs for symptomatic treatment. AHCHOS, as a mucus motility enhancer, can promote airway cilia oscillation, improve mucus clearance kinetics, and help expel phlegm 55 . According to the Chinese Children’s Medication Guidelines, AHCHOS is recommended for children with wet coughs, including bronchial asthma complicated with infection, persistent bacterial bronchitis, and pertussis 22,60 , and is one of the most important cough and phlegm relieving compound formulations suitable for children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine (TCM) has been widely used to treat lung diseases ( Tsai et al, 2013 ). Relevant studies have shown that TCM has obvious effects in alleviating ARDS pulmonary inflammation, reducing mortality and improving prognosis ( Yeh et al, 2021 ; Ting et al, 2022 ). Cepharanthine (CEP), a monomer component of TCM, is a natural alkaloid extracted from Step hania cepharantha Hayata , which has anti-inflammation, immunomodulation, antioxidation, anti-parasitic and anti-virus effects ( Murakami et al, 2000 ; Furusawa and Wu, 2007 ; Kudo et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%